2007
DOI: 10.1002/jso.20640
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy followed by surgery for squamous cell carcinoma of the thoracic esophagus with clinical evidence of adjacent organ invasion

Abstract: Aggressive multi-modal therapy with CRT followed by surgery in cT4 SCC of the thoracic esophagus is feasible. Surgery should be limited to patients with significant response to induction treatment and a high probability of R0 resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 33 publications
2
41
1
Order By: Relevance
“…As shown in Tables 1 and Table 3, seven studies [10][11][12][13][14][15][16] have analyzed the outcome of patients with T4 esophageal cancer who underwent CRT-S. Basically, the combination of 5-FU (200-1000 mg/m 2 ) and CDDP (5-100 mg/m 2 ) was used in all the studies as the primary chemotherapeutic regimen. Although the doses of concurrent radiation varied across studies (36-60 Gy), all CRT in the series were performed as a "planned" treatment before surgical resection.…”
Section: Chemo-radiotherapy Followed By Surgery (Crt-s) Regimenmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Tables 1 and Table 3, seven studies [10][11][12][13][14][15][16] have analyzed the outcome of patients with T4 esophageal cancer who underwent CRT-S. Basically, the combination of 5-FU (200-1000 mg/m 2 ) and CDDP (5-100 mg/m 2 ) was used in all the studies as the primary chemotherapeutic regimen. Although the doses of concurrent radiation varied across studies (36-60 Gy), all CRT in the series were performed as a "planned" treatment before surgical resection.…”
Section: Chemo-radiotherapy Followed By Surgery (Crt-s) Regimenmentioning
confidence: 99%
“…In the survival analysis according to infiltrated organs on pre-treatment staging, Manzoni et al 12) reported that curative resections were possible after CRT (50-60 Gy/ FP) in patients with tumor invasion of the aorta and no long survivors were observed in other categories; the 3-year survival time of patients with invasion of the aorta, airway, and others were 31.3, 4.5, and 0 months, respectively.…”
Section: Tumor Response and Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors concluded, aggressive multimodal therapy with ctrt followed by surgery in cT4 SCC of the thoracic esophagus is feasible. Surgery should be limited to patients with significant response to induction treatment and a high probability of R0 resection [8].…”
Section: Resultsmentioning
confidence: 99%